Penerapan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas 3 Di SDN 1 Mataram - Aprilia Pratiwi; Intan Triwahyuni; Syaiful Musaddat (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This study aims to enhance students' learning motivation by applying problem-based learning (PBL) model to thematic learning of Topic 7 in Class III in SDN 1 Mataram for the academic year 2022/2023. This type of study is a classroom study. Data collection methods use questionnaires and documentation. The type of data used is qualitative and quantitative data. The subjects of this study were the class III students of SDN 1 Mataram, a total of 29 students. The results of the study generally show that there is an increase in the percentage of educational motivation of students in the pre-cycle, when achieving results of 57% in the sufficient category (CT), then during the implementation of the first cycle it increases to 73%. in high category (T), and in the second cycle increases to 83% with very high category (ST), which means that the application of problem-based learning (PBL) teaching model is able to increase learning motivation Students of class III SDN 1 Mataram for 2022/ 2023 academic year.